STUDI PEMBENTUKAN RUANG KOMUNITAS PADA KAWASAN CAR FREE DAY RENON, DENPASAR - MADE ANGGITA WAHYUDI LINGGASANI; GDE BAGUS ANDHIKA WICAKSANA; NI KOMANG INDRA MAHAYANI; MADE DWI ARYA DAMAUTAMI; ANAK AGUNG AYU AMITHA DEWI (GANEC SWARA, 2024)
The purpose of this research is to understand how communal space develops in the Car Free Day (CFD) Renon in Denpasar, which transforms from a traffic space into a social space every week. Combination methods—also known as mixed methods—were used in this research. This method includes a qualitative approach through interviews and observations as well as a quantitative approach through surveys and questionnaires. The focus of the research is on physical space, how the space is used, social interactions, and the impact on the local community. The research results show that the distribution of communities in the CFD is relatively even, and the flow of visitor movement does not significantly affect the distribution of communities. Adequate public space, strategic and easily accessible locations, and opportunities for social interaction among communities are all factors that contribute to a positive community response. However, the issues faced by some communities include visitor congestion that reduces the efficiency of activities and the disorderliness of communal space arrangements in CFD. Therefore, gaining a better understanding of how CFD spaces are used can aid in better urban planning, improve urban quality of life, and encourage similar design efforts in other cities